Two tests of approach-iron golf skill and their ability to predict tournament performance - Robertson, S.; Burnett, A. F.; Gupta, R. (Journal of Sports Sciences, 2014)
The aim of this study was to investigate the convergent and predictive validity of two skill tests that examine the ability of golfers to hit accurate approach-iron shots. Twenty-four high-level golfers (handicap = 2.6 ± 1.7) performed the Nine-Ball Skills Test (assesses the ability to shape/control ball trajectory with high accuracy) and the Approach-Iron Skill Test (assesses the ability to hit straight shots from varying distances with high accuracy). Participants then completed at least eight rounds of tournament golf over the following 90 days and reported an indicator of approach-iron accuracy (per cent error index). A moderate correlation (r = 0.50, P < 0.05) was noted between scores for both tests. Generalised estimating equations, using two covariates (lie of the ball and distance to hole), were used to determine model fit and the amount of variance explained for tournament per cent error index. Results showed that the Approach-Iron Skill Test was the slightly stronger predictor of on-course per cent error index. With both test scores considered together, a minimal amount of additional variance was explained. These findings suggest that either of the tests used individually or combined may be used to predict tournament approach iron performance in high-level golfers